An Explorative Study on the Relationship between Learning Opportunities at School and at Work and Adolescents’ Mental Health - Karin Proost; Joris Van Ruysseveldt; Stef Adriaenssens; Dieter Verhaest; Dries Berings; Anja Van den Broeck (Psychologica Belgica, 2020)
Based on the Job Demands-Resources model, this study examined the association of learning opportunities of adolescents at school and work with their mental health, operationalized in terms of life satisfaction and depression. Intrinsic motivation at school and at work were studied as potential mediators. Within a representative sample of adolescents (n = 474), the results supported within domain relationships in the sense that learning opportunities at school and at work were positively related to intrinsic motivation at school and at work, respectively, which in turn were related to higher levels of life satisfaction and lower levels of depression. Cross-domain relationships were not significant, except for a negative relationship between learning opportunities at work and intrinsic motivation at school, suggesting that having a good job can pull students away from school.